First record of the invasive species Centaurea diffusa Lam. (Asteraceae) in high altitude wetlands, Valle de Uspallata, Mendoza - Tabeni, Solana; Scheibler, Erica Elizabeth; Bonjour, Lorena de Jesús (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
Centaurea diffusa is an invasive species whose distribution in Argentina covers the Pampean region. We report for the first time its presence in high altitude ecosystems at the Uspallata Valley in the province of Mendoza, Argentina. We provide a description of the specimens, photographic material and information about their habitat requirements and management status in Argentina and in America. Highlights Centaurea diffusa is recognized for being a species with ecological attributes of invasive plants. C. diffusa is native to Eurasia and their introduction in America has occurred accidentally by the entry into bags of alfalfa. The presence of C. diffusa in Argentina has been reported only in the Pampas region (Buenos Aires, Córdoba and La Pampa). We report for the first time its presence in high altitude ecosystems belonging to the Uspallata Valley in the province of Mendoza, Argentina.